2020
DOI: 10.1093/iwcomp/iwaa016
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Operator’s Decisions Based on Prospect Theory

Abstract: The aim of this work is to predict human operator’s (HO) decisions in a specific operational context, such as a cooperative human-robot mission, by approximating his/her utility function based on prospect theory (PT). To this aim, a within-subject experiment was designed in which the HO has to decide with limited time and incomplete information. This experiment also involved a framing effect paradigm, a typical cognitive bias causing people to react differently depending on the context. Such an experiment allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Theoretically, it has been shown that CPT is more "expressive" [17], "versatile", and "inclusive" [18] than CVaR and Expected Risk (ER), thus capturing a wider range of risk profiles of humans. Preliminary evidence that CPT better captures human decision making under risk can be found in applications of traffic intersection management and routing [19], and resource management settings by operators [20]. In practice, these approach is yet to be evaluated extensively in user studies pertaining navigation in RCE.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it has been shown that CPT is more "expressive" [17], "versatile", and "inclusive" [18] than CVaR and Expected Risk (ER), thus capturing a wider range of risk profiles of humans. Preliminary evidence that CPT better captures human decision making under risk can be found in applications of traffic intersection management and routing [19], and resource management settings by operators [20]. In practice, these approach is yet to be evaluated extensively in user studies pertaining navigation in RCE.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of such a MUM-T organization will require more cooperation and coordination between the agents, that could increase the mental workload of the human agent. However, there are immense advantages to this approach as for instance: benefiting from the faster and more calculative capabilities of the artificial agents, and for the human agents' better perception, judgment abilities and critical thinking (de Souza et al, 2020 ), increasing mission achievement chances while ensuring safety (Chanel et al, 2020b ), or enabling a better proximity and state awareness of the human agents (Strenzke et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%